Systems of systems: From mission definition to architecture description. Issue 6 (11th November 2019) - Cherfa, Imane; Belloir, Nicolas; Sadou, Salah; Fleurquin, Régis; Bennouar, Djamal
Abstract: Systems of Systems (SoS) encompass a group of distributed and independent systems. This class of systems requires recurrent adaptation at runtime owing to the uncertainty and variability of the runtime environment. Thus, during their execution, SoS can deviate from the initial specification, which is often a consequence of successive evolutions. This problem occurs mainly due to (a) weak communication between the SoS analysis stage and architecture stage and (b) the lack of links between the operational planning in the SoS analysis stage and systems that must be involved in the SoS architecture stage. This paper proposes a model‐based process that strengthens the links between the SoS analysis stage and the architecture stage in the wave life cycle. We ensure that the mission and role concepts for the SoS definition are sufficiently abstract to allow adaptation to the variability of the environment. This definition is translated into an abstract architecture that guides the choices of the system architect during the design and evolution stages. The proposed language is an adaptation of the Systems Modeling Language (SysML). Furthermore, we define a crowd management SoS to illustrate the process.